On the Origin of the 4.7 eV Absorption and 2.8 eV Emission Bands in Bulk AlN Substrates. (25th April 2016) - Alden, Dorian; Bryan, Zachary; Gaddy, Benjamin; Bryan, Isaac; Callsen, Gordon; Koukitu, Akinori; Kumagai, Yoshinao; Hoffmann, Axel; Irving, Doug; Sitar, Zlatko; Collazo, Ramon
Abstract : One of the main limitations based on point defects in AlN is related to the UV absorption band present at 265 nm. This relatively broad absorption band limits the use of bulk substrates within the deep UV range and several complicated fabrication procedures have been devised to overcome this limitation. The origin for this absorption band along with corresponding photoluminescence signatures will be reviewed. CN - and VN + were identified as the point defects directly associated with the main absorption at 4.7 eV and the emission at 2.8 eV. The main absorption is due to a transition between the CN - state and conduction band, while the emission arises from a DAP transition between the donor VN + and acceptor CN - through the 4.7 eV excitation channel. New observations based on photoluminescence excitation are presented to further support the assignments previously made.